123 Long-Term High-Frequency (10 kHz) Spinal Cord Stimulation in Painful Diabetic Neuropathy - A Randomized Controlled Trial. (1st April 2022) - Petersen, Erika A.; Stauss, Thomas; Scowcroft, James; Brooks, Elizabeth; White, Judith; Sills, Shawn; Amirdelfan, Kasra; Guirguis, Maged; Xu, Jijun; Yu, Cong; Nairizi, Ali; Patterson, Denis; et al.
Abstract : INTRODUCTION: World Health Organization estimates 422 million people with diabetes globally and approximately 20% with painful diabetic neuropathy (PDN). Current treatment options are ineffective for many patients; however, previous results suggest high-frequency (10 kHz) spinal cord stimulation (SCS) relieves pain and may improve sensation in patients with refractory symptoms. METHODS: Randomization of 216 patients assigned 1:1 to 10 kHz SCS (Nevro Corp.) combined with conventional medical management (CMM) or CMM alone. Patients had PDN symptoms ≥12 months, lower limb pain ≥5 cm (10 cm visual analog scale), and hemoglobin A1c ≤10%. Outcomes include pain, interference with daily activities and sleep, and neurological examination. Patients could opt to crossover to the other treatment arm at 6 months. RESULTS: At 6 months, 86% of patients in the 10 kHz SCS group were responders with at least 50% pain relief. They reported reduced pain interference with daily activities and improvements in sleep. None of the patients in the 10 kHz SCS group chose to crossover to CMM at 6 months. Treatment benefits were sustained through 12 months. A majority of patients treated with 10 kHz SCS were noted to have improvement on neurological examination. Participants in the CMM group experienced no change in pain levels, pain interference with daily activities, or sleep quality over 6 months. Eighty-two percent opted to crossover to 10 kHz SCS at 6 months. Results post-crossover were similar to those in patients originally randomized to 10 kHz SCS: 84% responders as well as reduced pain interference with daily activities, improvements in sleep, and a majority with observed improvements on neurological examination. CONCLUSION: This is the largest RCT to-date of SCS management in PDN. Substantial improvements with high-frequency (10kHz) SCS were sustained over 12 months and support this treatment for PDN patients with refractory symptoms.